Democracy, Prison, and Public Safety Realignment: Renewing Our Imagination - Turner, Kimberly (2014)
The American carceral condition has waged a 200-year-old struggle where the lives of the guilty, the innocent, and the victimized have taken center stage in a debate centered on rehabilitation, reformation, and revenge. The drama has undergone a number of revisions from great scholarly authors, multidisciplinary intellectuals, and literary muses. Despite a number of new renderings, the central themes of the American prison have remained constant, and just as there have been builders of prisons, there have been forces intent on their destruction. The current state of the American carceral condition has burgeoned since the neoliberal political and economic shift began in 1980. The State of California enjoys a political reputation as a socially liberal blue state, yet it is one of the national leaders in prison expansion, penal conservatism, and punitive excess. In 2011, California began the prison realignment system that includes sentencing restructuring and housing long- term felons in local county jails, thus shifting the financial burden and supervised release of inmates to local county Sheriff’s offices. The realignment is but one layer of the state’s response to the U.S. Supreme Court’s decision that California prisons violated the Eighth Amendment, in part, to overcrowding. The system is too young to reach definitive conclusions, but is at a crossroads. Either realignment will serve as another model for prison reformation and possibly prison abolition, or it will extend the carceral reach of the state into “free” space, essentially eliminating the wall, both literally and figuratively, that separates free souls from those held captive